2020
DOI: 10.2337/ds19-0046
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Profile in Indian Patients With Type 2 Diabetes: The Scope for Atherosclerotic Cardiovascular Disease Risk Reduction

Abstract: OBJECTIVE | Reduction of atherosclerotic cardiovascular disease (ASCVD) risk in patients with diabetes requires proper management of lipid parameters. This study aimed to find the pattern of dyslipidemia and scope of ASCVD risk reduction in patients with diabetes by lipid management.METHODS | Clinical, biochemical, and medication profiles of all patients with diabetes attending a tertiary diabetes care hospital over a 2-year period were collected. The prevalence of various lipid abnormalities was determined af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Maternal diabetes is a pathologic state that increases the incidence of complications in both the mother and the fetus ( Vrachnis et al, 2012 ), for example, low quality oocytes ( Zhang et al, 2013 ), increased chances of miscarriage ( Mills et al, 1988 ) and congenital malformations of offspring ( Vitoratos et al, 2010 ). Moreover, diabetic persons are considered to have significant positive relation for formation of hypercholesterolemia ( Chowdhury and Nessa, 2019 ) and high LDL cholesterol ( Jayakumari et al, 2020 ). Previous study has demonstrated that epigenetic inheritance via gametes by itself could increase an offspring’s susceptibility to develop to obesity and type 2 diabetes ( Huypens et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Maternal diabetes is a pathologic state that increases the incidence of complications in both the mother and the fetus ( Vrachnis et al, 2012 ), for example, low quality oocytes ( Zhang et al, 2013 ), increased chances of miscarriage ( Mills et al, 1988 ) and congenital malformations of offspring ( Vitoratos et al, 2010 ). Moreover, diabetic persons are considered to have significant positive relation for formation of hypercholesterolemia ( Chowdhury and Nessa, 2019 ) and high LDL cholesterol ( Jayakumari et al, 2020 ). Previous study has demonstrated that epigenetic inheritance via gametes by itself could increase an offspring’s susceptibility to develop to obesity and type 2 diabetes ( Huypens et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another study supported these findings that showed a significant correlation between lipid profile and HbA1c in diabetic patients associated with CVD. (17) This finding suggests that improved glycemic control, as shown by lower levels of FPG and HbA1C, would probably result in TG levels and lower LDL cholesterol in diabetic patients. As a result, medications for lowering lipid may be postponed till glycemic control is reached and a clearer representation of lipid pattern for patient is developed.…”
Section: Discussionmentioning
confidence: 99%
“…Newly diagnosed T2DM patients are commonly screened for the lipid profile and antilipidemic drugs are suggested if the levels are high for the individual [6]. Those who have their LDL cholesterol (LDL-C) in the normal range may have underlying risks of cardiovascular diseases associated with a higher percentage of sdLDL cholesterol (sdLDL-C) level.…”
Section: Introductionmentioning
confidence: 99%